Management of Staphylococcus aureus bacteraemia (SAB) in the oncology patient: Further evidence supports prompt removal of central venous catheters and shorter duration of intravenous antimicrobial therapy. Issue 1 (March 2020) - Dunne, Colum P.; Ryan, Phelim; Connolly, Roisin; Dunne, Suzanne S.; Kaballo, Mohammed A.; Powell, James; Woulfe, Bernie; O'Connell, Nuala H.; Gupta, Rajnish K.
Summary: Background: Staphylococcus aureus bacteraemia (SAB) is associated with relatively high risk of complications and high levels of mortality. Internationally, SAB management guidelines lack consensus and especially so regarding oncology patients. This is likely a reflection of insufficient randomised control trials (RCT) and the diversity of SAB patient populations. However, there are 2011 guidelines recommending a minimum of 14 days of appropriate IV antibiotic therapy for SAB. Objective: We wished to determine whether our practice of shortened duration of intravenous antimicrobial therapy in favour of oral administration proved as effective as recommended guidelines in a mixed oncology patient cohort. Methods: Retrospective review of patient records that included any SAB episode among oncology patients from January 2002 to December 2015. Medical chart reviews were undertaken to determine patient demographics, clinical management & antimicrobial therapy, duration of stay, presence of a central venous catheter (CVC) and outcome. Results: Our CVC removal rate was just 73% in SAB where CVC was the identified source of infection, with an attributable mortality rate (<4%) far lower than would be expected. Antimicrobial therapy durations were considerably lower (10 days) than current recommendations of 14 days IV therapy. The recurrence rate of 15% was also significantly lower than has been reported previously. Conclusions: Our observations contribute new insights concerning the management of SAB in oncology patients. Our findings suggest that therapeutic approaches should perhaps remain individualised and reflective of patient characteristics taking into consideration the complex nature of oncology patients.